Roger Nash Baldwin and the St. Louis Civil Liberties Trail: Celebrating 100 Years of the ACLU with a Search for the Organization’s Conceptual Founding - Patrick C. Brayer (Washington University Journal of Law & Policy, 2019)
This article traces the role of Roger Nash Baldwin as a leading figure in the American civil liberties movement in the early twentieth century. In particular, the article highlights the central role of St. Louis in this history. At the advice of family friend Louis Brandeis, Baldwin moved to St. Louis to become a sociology professor at Washington University. At the time, St. Louis was a center of migration for African Americans escaping oppression in the South. The article traces a variety of geographical locations throughout St. Louis that were important to Baldwin’s development as a leader in the civil liberties movement.
Keywords: civil liberties; St. Louis; Roger Nash Baldwin; ACLU; American Civil Liberties Union